Communication Within Families: Understanding Patterns and Impacts on Mental Health - Zadhasan, Zohreh (Journal of Psychosociological Research in Family and Culture, 2023)
Objective: This review aims to explore the dynamics of communication within families and its impacts on mental health, highlighting the role of various communication patterns in shaping mental well-being. Methods and Materials: Employing a descriptive narrative review approach, this article synthesizes contemporary literature from databases such as PubMed, PsycINFO, and Web of Science, focusing on studies published between 2000 and 2023. The selection criteria targeted empirical studies examining the relationship between family communication patterns and mental health outcomes across diverse cultural contexts. Findings: The review identifies key communication patterns within families, including open, supportive, and conflictual communications, and their significant impacts on mental health. It reveals that positive communication patterns are associated with better mental health outcomes, while negative patterns correlate with adverse mental health effects. The findings also underscore the importance of cultural and contextual factors in understanding these relationships. Conclusion: Strengthening family communication patterns offers a critical pathway to enhancing mental health. Future research should focus on developing targeted interventions that foster positive family communication and address the nuanced needs of diverse populations.